Blocking Notch1 signaling by RNA interference can induce growth inhibition in HeLa cells. Issue 2 (1st February 2007) - Yu, H.; Zhao, X.; Huang, S.; Jian, L.; Qian, G.; Ge, S.
Abstract : The Notch proteins constitute a family of transmembrane receptors that play a pivotal role in cellular differentiation, proliferation, and apoptosis. RNA interference of Presenilin1 (PS1) and Notch1 was carried out in this research to determine whether it could block Notch signaling and induce growth inhibition in HeLa cells. We transfected synthesized target small interfering RNA (siRNA) into HeLa cells, and blocking of Notch signaling was detected by C-promoter binding factor-1 (CBF1) reporter. We then conducted cell proliferation assay. Cells transfected with PS1 and Notch1 siRNA showed great inhibition in proliferation compared to the controls in vitro and in vivo . We conclude that RNA interference of PS1 or Notch1 can block Notch signaling and consequently induce growth inhibition of HeLa cells.